Imaging Rayleigh wave attenuation with USArray. Issue 1 (15th April 2016) - Bao, Xueyang; Dalton, Colleen A.; Jin, Ge; Gaherty, James B.; Shen, Yang
Abstract: The EarthScope USArray provides an opportunity to obtain detailed images of the continental upper mantle at an unprecedented scale. The majority of mantle models derived from USArray data to date contain spatial variations in seismic-wave speed; however, in many cases these data sets do not by themselves allow a non-unique interpretation. Joint interpretation of seismic attenuation and velocity models can improve upon the interpretations based only on velocity and provide important constraints on the temperature, composition, melt content, and volatile content of the mantle. The surface wave amplitudes that constrain upper-mantle attenuation are sensitive to factors in addition to attenuation, including the earthquake source excitation, focusing and defocusing by elastic structure, and local site amplification. Because of the difficulty of isolating attenuation from these other factors, little is known about the attenuation structure of the North American upper mantle. In this study, Rayleigh wave traveltime and amplitude in the period range 25–100 s are measured using an interstation cross-correlation technique, which takes advantage of waveform similarity at nearby stations. Several estimates of Rayleigh wave attenuation and site amplification are generated at each period, using different approaches to separate the effects of attenuation and local site amplification on amplitude. It is assumed that focusing and defocusing effects can be described by the Laplacian of the traveltime field. All approaches identify the same large-scale patterns in attenuation, including areas where the attenuation values are likely contaminated by unmodelled focusing and defocusing effects. Regionally averaged attenuation maps are constructed after removal of the contaminated attenuation values, and the variations in intrinsic shear attenuation that are suggested by these Rayleigh wave attenuation maps are explored.